Traumatic damage to the liver capsule: an unusual cause of small bowel obstruction. Issue 4 (26th April 2021) - Aloni, Kymberlie; Harris, Holly; Colucci, Gianluca; McFall, Malcolm
Abstract : A 61-year-old man presented to the emergency department with severe abdominal pain. Three months prior to presentation, he had sustained blunt trauma to his right side while cycling, but had not sought medical attention. On admission, a CT scan showed small bowel obstruction (SBO) and he underwent an emergency open laparotomy. Intraoperatively, a subcapsular liver haematoma was identified, with incarcerated, necrotic small bowel within the liver capsule. The patient underwent deroofing of the haematoma with an omental patch and a small bowel resection with primary anastomosis. We believe this is the first reported case of SBO secondary to small bowel herniation into the liver capsule following trauma.